BEING MUSLIM AND MOTIVATION IN LEARNING ARABIC: AN INSIGHT FROM THREE DECADES - Isral Naska (Islam Realitas: Journal of Islamic and Social Studies, 2017)
This article is a literature review on accessible three decades publicized studies about student motivation learning Arabic which was conducted in different countries and contexts. Due to the importance of Arabic in Islam as the sacred language, those research are expected to reveal the religious aspects in maintaining and shaping student motivation in learning Arabic. Unfortunately, the issue did not likely obtain adequate attention from most of the researchers. Interestingly though, review on that studies still managed to reveal that the researchers apparently mentioned the role of identity in their studies. However, it was not supported by the proper analysis which made only little can be recognized from the role of religious identity in shaping the motivation. This circumstance likely has taken place since most of the researchers did not use the poststructuralist approach which may bring them to reveal a deeper understanding of the role of identity in Arabic language learning. Furthermore, in order to obtain the more precise finding on the role of identity in maintaining student motivation, it is suggested to use the approach when addressing student motivation during Arabic learning process. Artikel ini adalah sebuah literatur review terhadap penelitian-penelitian tentang motivasi belajar Bahasa Arab sekitar 3 dekade belakangan yang dilakukan pada beberapa negara dengan konteks yang berbeda-beda. Peran Bahasa Arab sebagai bahasa yang penting dalam Islam, seharusnya mengantarkan penelitian yang ada mengungkap adanya aspek-aspek religiustitas dalam pembentukan motivasi belajar. Sayangnya, hal ini tidak mendapatkan perhatian yang cukup dari sebagian besar peneliti. Menariknya kendatipun hal tersebut terjadi, yaitu tidak tertangkapnya aspek religiusitas secara memadai, review terhadap hasil-hasil penelitian tersebut menunjukkan peran identitas religius para siswa tetap terlihat. Hanya saja hal tersebut tidak didukung oleh analisis yang memadai sehingga tidak banyak wawasan yang dapat diperoleh sekaitan dengan peran identitas religius tersebut. Hal ini terjadi karena kebanyakan peneliti tidak menggunakan pendekatan yang memungkinkan mereka mengeksplorasi peran identitas religius siswa dalam pembentukan motivasi belajar secara lebih mendalam, yaitu pendekatan post-structuralist. Dengan demikian, untuk memperoleh temuan yang lebih presisi, studi selanjutnya disarankan untuk menggunakan pendekatan post-structuralist untuk memahami peran identitas religius dalam pembentukan motivasi belajar Bahasa Arab